SOCIAL CHANGES IN THE REPUBLIC OF UZBEKISTAN - R.А.Nosirov (American Journals Publishing, 2024)
The article analyzes effective reforms in the social sphere in Uzbekistan, the issue of social protection of the population during the transition to a market economy, the main goal of all the reforms being carried out in the country, and today's issues of labor protection.
Keywords: Social sphere, reforms, independence, market economy, population, social protection, country.